Government Policy Regulating Land Acquisition Through the Land Bank According to the Job Creation Law - erni Rohaini; Lina Jamilah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The complexities of land concerns are a real issue that has yet to be handled. The fact that the amount of land available is fixed, while the desire for physical development grows in tandem with population growth, results in social conflicts that cannot be avoided. The battle of interest between the government, which requires land to build various infrastructures, and the people who wish to keep their rights to the property they own is one of the reasons for social conflict. As a result, it is required to reform land laws that direct the mechanism of integrated state land asset management that can simultaneously accommodate the needs of the government and the rights of community holders of land rights to achieve social justice for all Indonesians. Using the land bank concept as a way of integrated state land asset management may solve the development land dilemma. This study employs a normative legal approach and a descriptive qualitative analysis. In this study, it was revealed that the government's strategy on land purchase through the Land Acquisition Law could have been more effective in resolving land issues; hence, one land component was incorporated through the Job Creation Law via the Land Bank